Industry 4.0 Implementation in Automotive Sector: Driving Forces, Barriers and Competencies. Pilot Empirical Study - Anna MICHNA; Roman KMIECIAK; Joanna KRUSZEWSKA (Communications of International Proceedings, 2021)
The next step in industry development which is known as Industry 4.0 affects social, economic and technological environment. Together with new technologies and processes transformations, significant changes are also expected in employees’ competences as well as labour market. The aim of this article is to present results of a pilot empirical study which is the continuation of a previous theoretical study on the subject of forces, barriers and main competencies in regards to the implementation of Industry 4.0 solutions in manufacturing and services organizations. The data was collected in October 2021 and represents independent and voluntary convictions of employees, specialists, engineers and managers in regards to examined aspects. The practical dimension of this study is verification of a prepared tool, gathering survey participants’ comments in order to prepare a questionnaire for targeted research in the medium and small sized enterprises of the automotive sector in Poland.
Keywords: Industry 4.0; solutions; barriers; chances; driving forces; competencies.